A licenciatura em educação do campo da UFES e os desafios da permanência campesina no ensino superior - Duarte, Roberta Goncalves (2019)
This research aimed to understand the main reasons that have made it impossible for students from the Education Course to stay in the Campus of Goiabeiras’ neighborhood of the Federal University of Espírito Santo State (Ufes), as well as the paths to be followed to face this issue. According to the Ufes Education Information System, from the 354 students enrolled between 2014 and 2018, 28 formally dropped out, 39 were dismissed due to abandonment, about 40 were partly or not attending the academic activities in the first semester of 2018 and 1 student did a course re-option, which justified the need for this study. The theoretical methodological framework used is based on Paulo Freire and other popular education theorists. For data production, questionnaires, individual and collective interviews and shared analyzes were used, in line with the participant research assumptions, proposing actions that make it possible to contribute to the overcoming of the observed problems. The results indicated that the dropout in the course is a multifactorial phenomenon, as it occurs in general in the Brazilian Higher Education. Of the 14 categories of analysis that emerged, 10 are related to the challenges of student permanence and 4 refer to the pedagogical challenges of the course. Among the factors highlighted by the students as motivating the discontinuity of the studies are the lack of knowledge about the course, tensions and internal conflicts, difficulties in performing academic and work-related activities, family and financial problems, prejudice and non-recognition of the public power. Data demonstrate that the University is not yet ready to receive the working class, especially the peasants, who have different times, experiences, needs and perspectives. Since Education is a course composed mostly of women, the dialogues also denote a patriarchal view of society, in which women are seen as responsible for the care both of the family and home. Therefore, it is understood that student assistance policies should pay attention to the demands of students of poor backgrounds, offering support that dialogue with their realities.